Medicine pretest self-assessment and review - Urban, Robert S.; Pierce, J. Rush Jr; Smalligan, Roger D. (McGraw-Hill Education, 2016)
Medicine: PreTest Self-Assessment & Review is the perfect way for you to assess your knowledge of medicine/internal medicine for the USMLE Step 2 CK and shelf exams. It delivers 500 USMLE-style questions and answers that address the clerkship's core competencies along with detailed explanations of both correct and incorrect answers. All questions have been reviewed by students who recently passed the boards and completed their clerkship to ensure they match the style and difficulty level of the exam.